Effects of Vitamin D on Asprosin Immunoreactivity Against Cyclophosphamide- Induced Liver Injury in Rats - Turk, Ahmet; Kuloglu, Tuncay; Karadag, Abdullah; Metin, Tuba Ozcan (Springernature, 2023)
BackgroundCyclophosphamide (CP), commonly used as an anticarcinogenic drug, has the potential to induce detrimental effects on multiple tissues, including the liver. Asprosin, which is a glucogenic adipokine, induces the liver to secrete glucose, thus contributing to the maintenance of homeostasis. This study aims to investigate the immunoreactivity of asprosin in the liver tissue of rats exposed to CP administration, as well as the changes in its levels due to the supplementation of Vitamin D (Vit D).Materials and methodsFour experimental groups were formed, including control, Vit D (200 IU/kg), CP (200 mg/kg), and Vit D+ CP. Histopathological analysis was carried out by employing staining methods on liver tissues. These techniques encompassed the application of hematoxylin-eosin (H&E), Masson's trichrome, and periodic acid Schiff (PAS). Through the application of spectrophotometric methods, concentrations of malondialdehyde (MDA), total antioxidant status (TAS), total oxidant status (TOS), and asprosin were determined. Furthermore, apoptotic cells were identified by the terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) method, and the asprosin immunoreactivity was determined by immunohistochemistry. ResultsUnder light microscope examination, the histopathological damage was found to be more notable in the CP group compared to the control group. Moreover, a decrease was observed in serum and tissue asprosin levels, while an increase was noted in the count of apoptotic cells, along with elevated MDA and TOS levels. However, in the CP+Vit D group, Vit D administration alleviated histopathological damage. Notably, there were significant increases in TAS and asprosin levels, accompanied by reductions in both MDA and TOS levels.ConclusionsThe effect of CP on liver tissue was observed to result in damage and a reduction in asprosin levels. Vit D supplementation revealed elevated asprosin levels and a distinct protective effect on the tissue. Considering the association between asprosin and liver injury induced by CP, further research is needed to elucidate the mechanisms that underlie the effect of asprosin on tissues. When combined with Vit D, asprosin holds promise for potential clinical applications as a therapeutic target.
Keywords: asprosin; cyclophosphamide; liver damage; vitamin d; rat